Core Revelations: The Star Formation and Active Galactic Nucleus Connection at the Heart of NGC 7469 - Léa M. Feuillet; Steve Kraemer; Marcio B. Meléndez; Travis C. Fischer; Henrique R. Schmitt; James N. Reeves; Anna Trindade Falcão (The Astrophysical Journal)
We investigate the star formation–active galactic nucleus (AGN) connection in the Seyfert 1 NGC 7469 using James Webb Space Telescope mid-infrared spectroscopic integral field unit (IFU) data. We use the IFU data to generate maps of different emission lines present in the spectrum, such as the star formation (SF) tracer [Ne ii ] 12.81 μ m and the AGN tracer [Ne v ] 14.32 μ m. We can separate the AGN- and SF-dominated regions using spatially resolved mid-infrared diagnostic diagrams, and we further investigate the ionization sources powering each region by constructing photoionization models. We find that the previously detected eastern wind populates an intermediary region of the diagrams, between our star-forming and AGN points. Although it is possible that the star-forming ring may inherently not be uniform, this wind also coincides with a reduction in the [Ne ii ] emission in the ring, which suggests that the ionization cone intersects the ring in this direction.